A new fluorinated pyran-bridged A-D-A type small molecular acceptor for organic solar cells. (April 2020) - Li, Jun-nao; Wu, Yao; Zhang, Xiaolu; Zeng, Di; Luo, Yaling; Duan, Xianbao; Gao, Xiang; Cai, Ping; Zhang, Qi; Zhang, Jian; Liu, Zhitian
Abstract: A new fluorinated pyran-bridged A-D-A type small molecular non-fullerene acceptor, i-PTIC-F, is designed and synthesized. The optical and electrochemical properties have been well studied and compared with the non-fluorinated molecule, i-PTIC. The photovoltaic performance of i-PTIC-F is characterized using PBDB-T as the donor material. A reasonable power conversion efficiency of 5.68% is achieved with an enhanced J sc of 14.56 mA cm −2 . Graphical abstract: Image 1 Highlights: A new fluorinated acceptor based on pyran-bridged fused-ring was reported. The effects of fluorinated terminal groups were studied. Isomeric pyran-bridged fused-rings provide new building blocks for acceptors.